Common and Specific Abnormalities in Cortical Thickness in Patients with Major Depressive and Bipolar Disorders - Meiqi Niu; Ying Wang; Yanbin Jia; Junjing Wang; Shuming Zhong; Jiabao Lin; Yao Sun; Ling Zhao; Xiaojin Liu; Li Huang; Ruiwang Huang (2017)
Major depressive disorder (MDD) and bipolar disorder (BD) are severe psychiatric diseases with overlapping symptomatology. Although previous studies reported abnormal brain structures in MDD or BD patients, the disorder-specific underlying neural mechanisms remain poorly understood. The purpose of this study was to investigate the whole-brain gray matter morphological patterns in unmedicated patients with MDD or BD and to identify the shared and disease-specific brain morphological alterations in these two disorders. We acquired high-resolution brain structural MRI data from a sample of 36 MDD patients, 32 BD patients, and 30 healthy controls. Using FreeSurfer, we estimated their brain cortical thickness (CT) and compared between-group difference in multiple locations across the continuous cortical surface. Compared to the healthy controls, both the MDD and BD patient groups showed significantly reduced CT in the left inferior temporal cortex (ITC). However, compared to the MDD patients, the BD patients showed a significantly thinner CT in the left rostral middle frontal region. In addition, compared to the healthy controls, the BD patients displayed thinner CT in the left ITC, left frontal pole (FPO), left superior frontal, right lateral occipital, right pars triangularis (PTRI) and right lateral orbitofrontal regions. Further analysis revealed a significantly positive correlation between the mean CT in the left FPO and the onset age, but a negative correlation between the mean CT in the right PTRI and the number of episodes, in the BD patients. Our findings revealed that the BD and MDD patients had variations in CT that were in common, but many more that were distinct, suggesting potential differences in their neural mechanisms.